Pengembangan Enzyme-Linked Immunosorbent Assay Paratuberkulosis dengan Antigen Protoplasmik Mycobacterium avium Subspecies Paratuberculosis Isolat Lapang (DEVELOPMENT OF PARATUBERCULOSIS ENZYME-LINKED IMMUNO-SORBENT ASSAY WITH PROTOPLASMIC ANTIGEN OF MYCO - Adji, Rahmat Setya; Teguh Wawan, I Wayan; Lukman, Denny Widaya; Setiyaningsih, Surachmi (Jurnal Veteriner, 2015)
Enzyme-linked immunosorbent assay (ELISA) is a serological test method most widely used for thediagnosis of paratuberculosis, because it has a better sensitivity compared to other serological test.Protoplasmic antigen (PPA) or cellular extract is still the main choice for the diagnosis of paratuberkulosisdevelopment. The aim of research was to use the PPA Mycobacterium avium subspeciesparatuberculosis(MAP) field isolates for the development of paratuberculosis ELISA (ELISA PPA-L). As many as 322cattle sera (300 negative and 22 positive) were tested using this method and compared with IDEXXcommercial kit. The sensitivity and specificity of ELISA PPA-L test results were 68.18% and 97.0%,whereas for the IDEXX kit were 63.64% and 97.33%respectively. ELISA PPA-L had higher sensitivity andlower specificity compared to the IDEXX commercial kit. ELISA test using protoplasmic antigen of MAPfield isolates has good ability for paratuberculosis serological test and can be used for screening test of thedisease in Indonesia.
Keywords: ELISA, PPA, paratuberculosis, Mycobacterium avium subspecies paratuberculosis